Immigrant Gambling in Finland - Perpetual Crentsil (Suomen Antropologi)
An anthropological study of gambling among immigrant groups in Finland can reveal much about how the society organizes its way of life in categories  elevant for the economist, sociologist, political scientist and the historian. Anthropological studies of other aspects of immigrants’ lives—remittance giving, socio-economic status, and development issues in origin countries—usually present immigrants as ethnographic subjects. These lives are situated in specific historical and social conditions that represent particular images based on certain cultural values in their native homelands and in the place of settlement. Immigrant gambling has every potential to add to this corpus of knowledge.